A Quadrupolar Bis‐Triarylborane Chromophore as a Fluorimetric and Chirooptic Probe for Simultaneous and Selective Sensing of DNA, RNA and Proteins. Issue 10 (22nd January 2020) - Ban, Željka; Griesbeck, Stefanie; Tomić, Sanja; Nitsch, Jörn; Marder, Todd B.; Piantanida, Ivo
Abstract: A water‐soluble tetracationic quadrupolar bis‐triarylborane chromophore showed strong binding to ds‐DNA, ds‐RNA, ss‐RNA, as well as to the naturally most abundant protein, BSA. The novel dye can distinguish between DNA/RNA and BSA by fluorescence emission separated by Δ ν ˜ =3600 cm −1, allowing for the simultaneous quantification of DNA/RNA and protein (BSA) in a mixture. The applicability of such fluorimetric differentiation in vitro was demonstrated, strongly supporting a protein‐like target as a dominant binding site of 1 in cells. Moreover, our dye also bound strongly to ss‐RNA, with the unusual rod‐like structure of the dye, decorated by four positive charges at its termini and having a hydrophobic core, acting as a spindle for wrapping A, C and U ss‐RNAs, but not poly G, the latter preserving its secondary structure. To the best of our knowledge, such unmatched, multifaceted binding activity of a small molecule toward DNA, RNA, and proteins and the selectivity of its fluorimetric and chirooptic response makes the quadrupolar bis‐triarylborane a novel chromophore/fluorophore moiety for biochemical applications. Abstract : Boron finds DNA, RNA and BSA : A water‐soluble tetracationic quadrupolar bis‐triarylborane chromophore as ratiometric sensor for DNA/RNA and protein (BSA) is presented. This novel dye can distinguish between DNA/RNA and BSA by a characteristic fluorescence emission.